The Effect of Investment and Trade on Indonesian Economic Growth (Study on The Impact of The Russian – Ukraine War) - Burhanudin; Fitria, Dona; Budhy Saputro , Firdaus (PT. Maju Malaqbi Makkarana, 2024)
This study aims to analyze the effect of investment and trade on Indonesian economic growth with a focus on the impact of the Russian-Ukrainian war. The conflict between Russia and Ukraine has caused significant global uncertainty, affecting international investment and trade flows. This study employs a quantitative approach using secondary data from various official sources. Through regression analysis, it was found that investment and trade have a significant impact on Indonesia's economic growth. However, the instability caused by the Russian-Ukrainian war affects this relationship, particularly through changes in commodity prices and disruptions in global supply chains. The results of this study provide important insights for policymakers to develop strategies that can mitigate the negative impacts of international conflicts on the national economy.